Do trends of adiposity and metabolic parameters vary in women with different ovarian reserve status? A population-based cohort study. Issue 6 (June 2020) - Amiri, Mina; Ramezani Tehrani, Fahimeh; Rahmati, Maryam; Firouzi, Faezeh; Azizi, Feriedoun
Abstract: Objective: To investigate whether trends of adiposity and glucose metabolism parameters in women with low ovarian reserve status based on their anti-Mullerian hormone (AMH) levels differ from those with high ovarian reserve. Methods: In this population-based prospective study, eligible women, aged 20 to 50 years, were selected from among participants of the Tehran Lipid and Glucose Study (TLGS). Generalized estimating equation (GEE) models were applied to compare changes in various adiposity and metabolic parameters across time between women in the first and fourth quartiles of age-specific AMH, after adjustment for confounders. Pooled logistic regression was used to compare progression of prediabetes mellitus (pre-DM) and diabetes mellitus (DM) between the women of these two age-specific AMH quartiles. Results: In this study of a total of 1, 015 participants and with a median follow-up of 16 years, we observed that over time, both groups of women in the first and fourth quartiles of age-specific AMH experienced significant positive trends in their adiposity indices including central obesity, waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), a body shape index (ABSI), and a negative trend in visceral adiposity index (VAI), whereas there was no significant difference in these parameters between the two groups. This study revealed that odds ratios of diabetes and prediabetes in women in the first quartile of age-specific AMH were not significantly different, compared with those in the fourth quartile. Conclusion: Women with lower ovarian reserve do not experience different over time trends of adiposity and glucose metabolism parameters during their reproductive life span.